Classification and management of animal anthrax outbreaks based on the source of infection - Antonio Fasanella (Annali dell'Istituto Superiore di Sanità)
Anthrax is a non-contagious infectious disease; it primarily affects herbivores, but all mammals, including humans, can be affected. Humans may contract anthrax directly or indirectly from infected animals. Veterinary surveillance systems, providing information about animal and human cases, should increase the efficacy of the animal anthrax management in order to protect population. Any aspect of the disease should be carefully monitored to implement effective prevention and control strategies. In this paper we propose a new, detailed classification of anthrax outbreaks, based on the source of the infection and the risk level for humans. We describe three different types of animal outbreaks and suggest the most effective procedures for their management and prevention.